Determinants of Child Marriage in Indonesia : A Systematic Review - Zulfa Zuhriyyah Ayudiputri; Anisa Afianti Nur; Siska Amanda; Fahma Fadila Hanifa (Universitas Airlangga, 2024)
Early marriage is an ongoing phenomenon and is becoming more prevalent. The lack of public knowledge and lack of awareness of early child marriage leaves children deeply traumatized. More than 1 million (1.2 million) women aged 20-24 were married for the first time before the age of 18. The purpose of this study was to provide an overview of the causal characteristics of child marriage in Indonesia. The method used in this study was a systematic review conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) rules. The literature search was performed across multiple journal sites or online articles such as Google Scholar, PubMed, and Science Direct by entering the keywords 'Determinants of child marriage AND Indonesia'. There is a prevalent belief among parents and youth is that marrying off young girls preserves family honor. Additionally, poverty and economic instability make child marriage more socially acceptable. Other contributing factors include limited access to education and societal norms that promote marriage after puberty and within the same ethnic group. Despite existing laws regulating the minimum age for marriage, enforcement remains problematic. The review of nine articles indicated that child marriage in Indonesia is influenced by beliefs, limited access to education, culture, environmental factors, and gaps in legal enforcement.